Added value of fetal MRI in fetuses with suspected brain abnormalities on neurosonography: a systematic review and meta-analysis. (16th September 2016) - van Doorn, Martine; Oude Rengerink, Katrien; Newsum, Esther A.; Reneman, Liesbeth; Majoie, Charles B.; Pajkrt, Eva
Abstract: Purpose : To evaluate the additional diagnostic value of fetal Magnetic Resonance Imaging (MRI) in fetuses with suspected brain abnormalities identified with advanced neurosonography (NS). Methods : A systematic literature search was performed for studies reporting on a comparison between diagnosis with NS and MRI, in fetuses suspected for brain abnormalities. Abnormalities detected on NS were compared with those detected on MRI as well as with postnatal imaging findings to assess the added value of fetal MRI. Results : We included 27 articles, reporting on 1184 cases in which NS and MRI diagnosis were compared. In 65% of cases [773/1184] fetal NS and fetal MRI diagnosis agreed completely. In 23% [312/1184], MRI showed additional or different pathology. In 8% [99/1184], MRI rejected the NS diagnosis with normal brain as conclusion. For 454 cases a comparison with postnatal imaging could be made. Compared to the postnatal diagnosis, fetal MRI diagnosis agreed completely in 80% [364/454] and fetal NS in 54% [243/454] (difference 27%, 95% CI 21–33%). Additional abnormalities were found on postnatal imaging in 36% [164/454] after NS and in 14% [61/454] after fetal MRI. Conclusions : This meta-analysis shows that fetal MRI in addition to NS improves diagnostic accuracy in detecting brain abnormalities.